Field-Identification IAT predicts students’ academic persistence over and above Theory of Planned Behavior constructs - Roland, Nathalie; Mierop, Adrien; Frenay, Mariane; Corneille, Olivier (Frontline Learning Research, 2018)
Ajzen and Dasgupta (2015) recently invited complementing Theory of Planned Behavior (TPB) measures with measures borrowed from implicit cognition research. In this study, we examined for the first time such combination, and we did so to predict academic persistence. Specifically, 169 first-year college students answered a TPB questionnaire and completed a field-identification Implicit Association Test (IAT). The IAT measure largely predicted academic persistence 6 months later over and above TPB constructs, including behavioral intention. We discuss interpretations of this finding and its relevance to educational research.